PENGEMBANGAN KETERAMPILAN SOSIAL BERBASIS MOTIVASI BERWIRAUSAHA DALAM PENGOLAHAN SAMBAL SAGELA DI PKBM PLAMBOYAN KOTA GORONTALO - Rusdin Djibu (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2023)
This study aims to improve social skills based on entrepreneurial motivation in the processing of sambal sagel at PKBM Plamboyan Gorontalo City with four main objectives: knowing the objective conditions of developing social skills, designing a conceptual model for developing social skills, implementing the model for developing social skills, and evaluating the effectiveness of the development model. social skills. This study uses a qualitative and quantitative approach with the R and D method and post-test evaluation showing the effectiveness of developing an empowerment model by increasing learning achievement of members and entrepreneurial behavior